Listening for Madeleine: a portrait of Madeleine L'Engle in many voices - Marcus, Leonard S. (Farrar, Straus and Giroux, 2012)
"A book of interviews with people who knew Madeleine L'Engle, author of the children's classic A WRINKLE IN TIME, in the many facets of her life"--